Diabetes Care Disparities: The Impact of Lifestyle, Medication Access, and Medical Conditions on Glycemic Control in Rural and Urban Settings - Mohammad Reza Taherian; Koorosh Etemad; Soheila Sadeghi; Goljamal Jorjani; Seyed Saeed Hashemi Nazari (Journal of Diabetes Research, 2025)
Conclusions: These findings underscore the significance of geographic disparities, medication access, lifestyle practices, and dietary behaviors in diabetes management. Targeted interventions tailored to these factors are essential to improve glycemic outcomes in Type 2 diabetes.